Improving Science Learning by Applying the Natural Environment Approach into the Characteristics of Living Things Chapter - Muhammad Zefri Sani Nasution; R. Hariyani Susanti; Muhammad Ilham Syarif (Journal of Learning Improvement and Lesson Study, 2022)
This research is prompted by the lack of understanding of science subject students within the chapter of Characteristics of Living Things in grade IV of 064955 Medan primary school in the academic year of 2022/2023, which consists of 26 students. At the pre-cycle stage, the learning method used was traditional and not engaging. The aim of the research is to improve the students' natural science learning through the application of the natural environment approach, students learn outside the classroom by observing plants and animals in the environment around the school. Implementation of remedial research carried out over 2 cycles. Each cycle found an increase in the improvement of science learning. The increase in the improvement of science learning in each cycle can be seen from the attitude of students who are active, diligent and able to do assignments well and on time. Study results show an increase in the average value of each cycle, at pre-cycle at 63.23, cycle 1 at 67.3 and cycle 2 at 76.5. In terms of completeness, it can be seen from the increase in percent, in pre-cycle it achieved 30.7%, cycle 1 achieved 61.5% and cycle 2 reached 100%. The conclusion of this study through the application of an environmental approach can improve student learning in the subject of Characteristics of Living Things in grade 4